The relationship between personality traits and willingness to undergo cosmetic surgery in the non-clinical population – a systematic review and meta-analysis - Lăzărescu, Gianina-Mălina; Vintilă, Mona (Frontiers in Psychology, 2023)
Objective. Conducting a systematic review and meta-analysis to synthesize previously obtained results regarding the relationship between interest in cosmetic surgery and personality traits. Methodology. A series of criteria were applied (at the level of design, independent variables, dependent variable, and participants) for the studies included in the meta-analytic approach in order to be considered eligible. The identification of research that meets the eligibility criteria was carried out with the help of an electronic search in the following databases: ScienceDirect, PsycINFO, Web of Science, Scopus, Springer, and PubMed. Following this approach, 13 studies remained subject to the final analysis and were included in the meta-analysis. Results. Following the analyzes carried out, the researchers' expectations were partially supported by the results, proving the existence of a significant relationship between neuroticism, perfectionism, appearance-based rejection sensitivity, and the interest in following an aesthetic surgery. Discussion and recommendation. Identifying these relationships will allow plastic surgeons to understand the mechanisms underlying this choice and the need for psychological assessment/counseling before undergoing such a procedure. It will also allow psychologists to make specific best practice guidelines for approaching the patient before undergoing cosmetic surgery. At the same time, psychotherapists can develop specific personalized interventions for each personality profile, so that the decision to undergo an aesthetic operation is not made based on a dispositional trait (fear of rejection, increased curiosity, stress caused by body dissatisfaction).